Isolation of Hemicellulose from Oil Palm Empty Fruit Bunches (Elaeis guineensis Jacq.) and Its Application as a Gelling Agent in Topical Gel Formulations - Sitompul, Maysaro; Dalimunthe, Gabena Indrayani; Rani, Zulmai; Miswanda, Dikki (Pustaka Media Publishing, 2025)
This study aimed to isolate hemicellulose from oil palm empty fruit bunches (OPEFB) (Elaeis guineensis Jacq.) and evaluate its potential as a gelling agent in topical gel formulations. Hemicellulose was extracted using alkaline treatment with varying NaOH concentrations (0.05–0.5 N). The highest yield of 12.84% was obtained at 0.5 N NaOH. The isolated hemicellulose was then formulated into five gel preparations using hemicellulose alone, Carbopol 940 alone (2%), and their combinations at different ratios. All formulations were evaluated for organoleptic properties, homogeneity, spreadability, adhesiveness, pH, and viscosity over 14 days. The results showed that all gels were homogeneous with acceptable physicochemical properties. Spreadability ranged from 5.3–6.7 cm, adhesiveness from 2.02–2.66 seconds, and viscosity from 2,470–32,800 cPs. Most formulations maintained pH values within the ideal skin range (4.5–6.5). Combination formulations exhibited better gel characteristics than hemicellulose alone, indicating a synergistic effect with Carbopol 940. This research demonstrates that hemicellulose derived from OPEFB can serve as a promising natural gelling agent in pharmaceutical gels. The utilization of this agricultural waste offers a sustainable and environmentally friendly alternative to synthetic excipients while adding economic value to oil palm biomass.